Entrepreneurial Venture: Developing Aloe Vera Health Drinks in Sekarpuro Village, Malang - Agustina, Rini; Dodit Suprianto; Tiffany Azhar Izzuddin (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
This community service aims to increase the use of aloe vera as a basic ingredient for health drinks, to provide added economic value to the community while supporting a healthy lifestyle. This activity was carried out in the Sekarpuro Village community, which has great potential in cultivating aloe vera, but so far has only been utilized to a limited extent. Through training in processing aloe vera into healthy drinks, the community was given an understanding of processing techniques, starting from selecting quality aloe vera, processing aloe vera gel, to adding supporting ingredients such as syrup to improve the taste. In addition, the health benefits of aloe vera were also conveyed, which include improving the digestive system, body hydration, and immunity. The results of this activity showed an increase in community skills in processing aloe vera into marketable beverage products and an increase in understanding of the health benefits of aloe vera. It is hoped that through this program, the community will be more motivated to utilize existing local potential and expand the marketing of aloe vera beverage products as part of promoting a healthy lifestyle.